2008
DOI: 10.1002/ccd.21703
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter coil occlusion of perimembranous ventricular septal defects

Abstract: Transcatheter coil occlusion of a VSD can be performed reliably and safely by selecting appropriate embolic coils. Small defects (<2.5 mm) can be closed with a flipper coil, but defects >or=2.5 mm require a 0.052'' coil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
0
9
1
Order By: Relevance
“…Afterwards, other cardiologists followed his lead and used Rashkind’s double-disc patent ductus arteriosus (PDA) umbrella, Rashkind’s ASD double-umbrella, and clamshell devices for transcatheter occlusion of VSDs 21 26 . Subsequently, other devices were used to percutaneously occlude the VSDs: buttoned device (Custom Medical Devices, Amarillo, TX, USA) 27 , 28 , CardioSEAL and STARFlex devices (Nitinol Medical Technologies, Inc., Boston, MA, USA) 29 , Nit-Occlud device (pfm - Produkte für die Medizin AG, Köln, Germany) 30 – 33 , Amplatzer Muscular VSD Occluder device (St. Jude Medical, Inc., St. Paul, MN, USA) 34 – 39 , detachable steel coils (Cook, Bloomington, IN, USA) 40 , Gianturco coils (Cook) 41 , flipper, 0.052ʺ Gianturco, or 0.035ʺ platinum coils (Cook) 42 , wireless devices such as detachable balloon and transcatheter patch (Custom Medical Devices) 43 , Amplatzer Duct Occluder (St. Jude Medical, Inc.) 44 , Shanghai symmetrical perimembranous VSD occluder (Shape Memory Alloy Ltd., Shanghai, China) 45 , Amplatzer Duct Occluder II (St. Jude Medical, Inc.) 46 56 , Cera devices (Lifetech Scientific Co. Ltd., Shenzhen, China) 57 , and perhaps other devices (not known to the authors).…”
Section: Ventricular Septal Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterwards, other cardiologists followed his lead and used Rashkind’s double-disc patent ductus arteriosus (PDA) umbrella, Rashkind’s ASD double-umbrella, and clamshell devices for transcatheter occlusion of VSDs 21 26 . Subsequently, other devices were used to percutaneously occlude the VSDs: buttoned device (Custom Medical Devices, Amarillo, TX, USA) 27 , 28 , CardioSEAL and STARFlex devices (Nitinol Medical Technologies, Inc., Boston, MA, USA) 29 , Nit-Occlud device (pfm - Produkte für die Medizin AG, Köln, Germany) 30 – 33 , Amplatzer Muscular VSD Occluder device (St. Jude Medical, Inc., St. Paul, MN, USA) 34 – 39 , detachable steel coils (Cook, Bloomington, IN, USA) 40 , Gianturco coils (Cook) 41 , flipper, 0.052ʺ Gianturco, or 0.035ʺ platinum coils (Cook) 42 , wireless devices such as detachable balloon and transcatheter patch (Custom Medical Devices) 43 , Amplatzer Duct Occluder (St. Jude Medical, Inc.) 44 , Shanghai symmetrical perimembranous VSD occluder (Shape Memory Alloy Ltd., Shanghai, China) 45 , Amplatzer Duct Occluder II (St. Jude Medical, Inc.) 46 56 , Cera devices (Lifetech Scientific Co. Ltd., Shenzhen, China) 57 , and perhaps other devices (not known to the authors).…”
Section: Ventricular Septal Defectsmentioning
confidence: 99%
“…Although CardioSEAL Septal Occlusion System with QwikLoad and the STARFlex Septal Occlusion System have received FDA approval in the past, they are not widely used at present. Free and detachable Gianturco coils 41 , 42 , Nit-Occlud device 30 – 33 , 75 , Amplatzer Duct Occluder 44 , and Amplatzer Duct Occluder II 46 56 are also being used on an off-label basis. Discussion of devices used on an off-label basis will not be included in this review; the interested reader may review the respective publications 30 – 33 , 41 , 42 , 44 , 46 56 , 75 .…”
Section: Ventricular Septal Defectsmentioning
confidence: 99%
“…[2126] Some authors reported ASD and VSD closures as the former procedure of a combined intervention, with an embolization of a PDA or a pulmonary balloon valvuloplasty performed after those procedures. [182728] In our study, coil embolization of ductus in four and coarctation balloon angioplasty in one patient were successfully performed as second procedures of combined interventions after percutanous VSD closure as the first procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] It is categorized according to the location of the principal lesion in the interventricular septum. 5 Surgical closure of VSD has been the treatment of choice in the majority of cases. 4 Subjects with untreated VSD carry a high risk of developing complications such as infective endocarditis, which has a reported incidence of 14.5 per 10 000 patient-years.…”
Section: Introductionmentioning
confidence: 99%
“…Three main types of VSD are perimembranous, muscular, and supracristal, with perimembranous VSD being the most common type. 5,6 However, postsurgical residual VSD has been reported in 9-36% of all VSDs undergoing surgical repair. 5 Surgical closure of VSD has been the treatment of choice in the majority of cases.…”
Section: Introductionmentioning
confidence: 99%